Towards green energy societies ; prospects and challenges of solar energy driven development in Zimbabwe. - Mutisi, Zodwa (Midlands State University, 2020)
Solar energy is gaining momentum because of myriad challenges the world is facing as a result of climate change. Globally various efforts have been muted to ameliorate the effects of climate change among them, the ongoing international engagements under the banner of United Nation Framework Convention on Climate Change (UNFCCC). Various outcomes of these engagements include among other outcomes, the embrace of renewable energy to both address the bedeviling energy challenges and to reduce greenhouse gas (GHG) emissions. Globally, parties to the UNFCCC have committed to nationally determined contributions (NDCs) which, in many countries have been rooted in addressing the ways nations drive their development especially in the energy sector. The research is premised in the qualitative paradigm with the interest to understand the prospects, development, embrace, and challenges of solar energy in Zimbabwe. It employs an exploratory qualitative research design which draws data from oral interviews in order to fully understand the development and transition from conventional energy driven development towards solar energy driven development in Zimbabwe. The focus of the study is on the main players in the solar energy sector which include solar energy companies in Harare, Ministry of Energy and Power Development (MEPD), Zimbabwe Energy Regulatory Authority (ZERA) and other supporting institutional formations which influence the sector. The research established that, the transition from fossils driven development to renewable energy is spreading rapidly given the challenges conventional sources of energy are facing. In Zimbabwe, solar energy is becoming more indispensable in extending access to electricity energy to about 68% of the population residing in rural areas. Off grid solar energy initiatives are poised to transform the energy situation of the rural majority of the Zimbabwean population. In the same vein, the research also established that the renewable energy sector in Zimbabwe is still littered with structural impediments despite concerted efforts by the responsible institutional formations to make it navigable and lucrative. The research ends by recommending that though solar is highly promising, various structural formations should be put in place to cushion consumers from poor technologies and rogue players in the solar energy sector in order to make the transition sustainable.